1490. Serious Infections Caused by Carbapenem Susceptible and Carbapenem Resistant Acinetobacter baumannii-calcoaceticus Complex - A Retrospective Review. (31st December 2020) - Rana, Khurram; Wunderink, Richard G; Tsuei, Betty J; Rahav, Galia; Kovalchuk, Eugenii; Koksal, Iftihar; Maloney, Kathleen; Srinivasan, Subasree
Abstract: Background: Increasing resistance to available antibiotics, including carbapenems, is limiting effective treatment options for serious Acinetobacter baumannii-calcoaceticus (ABC) complex infections that are associated with high mortality. This multi-center retrospective analysis is to describe the natural history and outcomes of serious ABC infections. Methods: This was a retrospective review of 125 cases of ABC infections from United States (US), Israel, Turkey and Russia. Baseline, microbiologic, treatment and outcomes data were collected from patients with hospital-acquired (HABP, n=23) or ventilator-associated bacterial pneumonia (VABP, n=26), bacteremia (n=36), urinary tract infections/acute pyelonephritis (n=16), and wound ABC infections (n=24) between 2017-2019. Results: Fifty percent of cases reviewed were from the US. The median age of patients was 63 years (range 18-93), 46% were > 65 years old, 69% were male, 31% had renal failure, and 22% had septic shock. The most common co-morbidities observed were cardiac disease (41%), diabetes (32%) and moderate or severe renal disease (26%). Rates of resistance were observed as follows: ciprofloxacin 74%, ceftazidime 67%, amikacin 52% and colistin 0%. Carbapenem resistance (CR) was observed in 49% of patients. Most patients (73%) received combination therapy with 37% receiving at least 4 antibiotics. Carbapenems (40%) and penicillin/b-lactamase inhibitors (42%) were mostly used for treatment. Polymyxins were used in 18% of cases. Overall, the 28-day mortality was 34% and was highest in bacteremia (56%) and VABP (50%). CR appears to be a factor in mortality and other outcomes, as well as hospital days (table). In patients who received monotherapy, all 5 patients with CR infection died compared to 29% mortality in patients with carbapenem sensitive (CS) infection. Mortality was 70% in 20 cases when colistin was used for treatment. Conclusion: Serious ABC infections are associated with substantial comorbidities and a high mortality rate despite treatment with combination therapy. CR appears to be a major factor in mortality. New antibiotics are urgently needed to treat serious ABC infections. Disclosures: Khurram Rana, PharmD, Entasis Therapeutics (Employee) Galia Rahav, MD, AstraZeneca (Scientific Research Study Investigator) Kathleen Maloney, CCRP, Entasis Therapeutics (Employee) Subasree Srinivasan, MD MPH, Entasis therapeutics (Employee)